Endovascular solutions for type IA endoleak after endovascular aneurysm repair - Isabel Maria da Costa Viana (2021)
Introduction: Endovascular aneurysm repair (EVAR) has largely overcome open surgery for Abdominal Aortic Aneurysm (AAA) repair and stands for the preferred method. Type IA endoleak (E1A) is a well-known EVAR-specific complicate with an incidence of 3.5-15.5%. There is consensus on the expedite need for E1A correction due to continuous sac pressurization. Many possible approaches are available to correct E1A. The present review aims to describe endovascular options for E1A repair. Material and methods: MEDLINE databases were searched in order to find the available evidence on the management of persistent E1A. The research included articles between January 2010 and October 2020. Results: Seventeen studies were included with a total of 320 patients. The primary technical success was higher with Endovascular Aneurysm Sealing with or without chimney, with endoleak sealing rates up to 100%. Regarding reintervention rates, EndoAnchoring presented fewer incidence. Freedom from endoleak at the end of follow-up (FU) was higher with proximal cuffs and Chimney EVAR (ChEVAR). For conservative approach, the results show reintervention rates between 4-11% and freedom from endoleak at the end of FU with or without treatment around 90%. Conclusions: Several techniques are currently available for E1A repair. Nonetheless, larger studies are needed to understand which techniques are better for each case.